Strategies of Christian Religious Education Teachers in Instilling Biblical Literacy Among Fourth-Grade Students at SDN 1 Panarung, Palangka Raya - Yumi; Tirta Susila; Sinta Nurlela (CV. Edujavare Publishing, 2026)
This study aims to describe the strategy of Christian Religious Education teachers in instilling Bible literacy in grade IV students at SDN 1 Panarung Palangka Raya. This research is motivated by the low interest in reading the Bible among students, the lack of understanding of the content and message of the Bible, and the lack of optimal learning strategies applied by teachers in instilling Bible literacy. The research method used is a qualitative approach with a descriptive type of research. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study show that the strategies used by Christian Education teachers include interactive storytelling methods, regular Bible reading habits, assignments through spiritual activity books, and assistance to students in understanding and applying biblical values in daily life. The cultivation of Bible literacy is carried out through the habit of reading the Bible before the study begins, providing an understanding of the content and message of the Bible, and the assignment of spiritual activities that support the habit of reading the Bible at home